1978
DOI: 10.1063/1.89877
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of nonthermal ion energy in laser-generated plasma

Abstract: Plasma was generated by focusing a 1.06-μm 35-psec laser pulse obliquely onto a solid surface at the optimum resonance absorption angle. The scaling of nonthermal ion emission energy with laser intensity was determined. A computer model for resonance absorption showed nonthermal ion emission to be due to electron acceleration by a resonantly driven electrostatic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In tkese conditions it seems reasonable to think that they are formed of H + and C" so that the ratio mass/charge is between 1 and 2 thus increasing the estimated values. At high intensities on the other hand, it has been shown that fast ions are mainly H+ [21].…”
mentioning
confidence: 99%
“…In tkese conditions it seems reasonable to think that they are formed of H + and C" so that the ratio mass/charge is between 1 and 2 thus increasing the estimated values. At high intensities on the other hand, it has been shown that fast ions are mainly H+ [21].…”
mentioning
confidence: 99%
“…If it is not known, the depth can be chosen from prior knowledge of fast ablator ions from similar shots and the process is repeated if the fast ablator ion tracks reappear. This technique leverages the "bulketch" procedure (an etch where the bulk removal rate is roughly equal to the track etch rate 8,13,14 ) for removing CR-39 material and erasing the tracks from the original "track-etch" (an etch which preferentially develops particle tracks), and is used in applications like track coincidence counting. 13 The track etch itself has an associated bulk removal rate, roughly 2.6 µm/h.…”
Section: Data Recovery Proceduresmentioning
confidence: 99%
“…4,5 Much effort has been devoted to the study of the empirical conditions which drive these instabilities and how maximum ion energy scales with laser intensity. [6][7][8] On-target laser intensities approaching 10 15 W/cm 2 in OMEGA ICF implosions result in fast ablator ion energy endpoints of order ∼1 MeV. 9 Certain HED plasma experiments at OMEGA and the National Ignition Facility (NIF) have configurations with unique geometries and unusually high laser intensity which result in large fast ablator ion energies.…”
Section: Introductionmentioning
confidence: 99%
“…Charged-particle measurements have demonstrated that the energies of particles from certain types of implosions exceed their theoretical birth energies by 0.5 MeV or more 4,5,17,29,30,32 ͑see Fig. 26͒.…”
Section: Particle Energy Modification Through Electrostatic Accelerationmentioning
confidence: 99%